(untitled) (Scientific journal of the Fergana State University, 2026)
The aim of this study is to conduct a scientific analysis of the potential for effectively implementing a ratchet mechanism-based tourniquet—characterized by its modern design, ergonomic features, and rapid usability—into military medicine and civilian healthcare systems. The study explores the advantages of this device in quickly and reliably stopping hemorrhage in emergency situations and proposes ways to enhance the effectiveness of existing tourniquet models. Analytical and comparative methods were used to evaluate its application in the practice of the Uzbekistan Armed Forces. The construction, operating principles, and benefits of ratchet tourniquets used in foreign military systems, particularly in the U.S. Army, were examined. A comparative analysis with traditional tourniquets was also conducted from technical and operational perspectives. The findings indicate that the ratchet mechanism enables quick, one-handed application, providing a significant advantage in combat conditions. The article also presents information on the integration of the tourniquet directly into military uniform components. In conclusion, the introduction of such tourniquets into the national army could significantly increase the survival rate of injured personnel and may also be useful in civilian medicine during emergency situations.